2008
DOI: 10.1111/j.1469-8137.2008.02540.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐distance transport of mRNA via parenchyma cells and phloem across the host–parasite junction in Cuscuta

Abstract: Summary• It has been shown that the parasitic plant dodder (Cuscuta pentagona) establishes a continuous vascular system through which water and nutrients are drawn. Along with solutes, viruses and proteins, mRNA transcripts are transported from the host to the parasite. The path of the transcripts and their stability in the parasite have yet to be revealed.• To discover the route of mRNA transportation, the in situ reverse transcriptasepolymerase chain reaction (RT-PCR) technique was used to locally amplify ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 31 publications
2
74
0
Order By: Relevance
“…The RNA silencing signal in plants also moves across graft junctions (Palauqui et al, 1997;Voinnet and Baulcombe, 1997). RNAs have been shown to freely translocate between parasitic plants and their hosts (Roney et al, 2007;David-Schwartz et al, 2008). For example, a b-glucuronidase silencing signal generated by the host roots was translocated across the haustorium and was shown to be functional in the facultative root parasite Triphysaria (Tomilov et al, 2008).…”
Section: Cross-species Rnai Of the Dodder Stm Genementioning
confidence: 99%
See 2 more Smart Citations
“…The RNA silencing signal in plants also moves across graft junctions (Palauqui et al, 1997;Voinnet and Baulcombe, 1997). RNAs have been shown to freely translocate between parasitic plants and their hosts (Roney et al, 2007;David-Schwartz et al, 2008). For example, a b-glucuronidase silencing signal generated by the host roots was translocated across the haustorium and was shown to be functional in the facultative root parasite Triphysaria (Tomilov et al, 2008).…”
Section: Cross-species Rnai Of the Dodder Stm Genementioning
confidence: 99%
“…Furthermore, RNAi offers the advantages of being applicable to silencing of multigene family members and homologs in polyploids (Lawrence and Pikaard, 2003). It has been demonstrated that RNAs freely translocate between parasitic plants and their hosts (Roney et al, 2007;David-Schwartz et al, 2008). Thus, expression of RNAs that debilitate parasite development upon uptake, or RNAi in the host of target gene sequences specific to the parasite, are both strategies that are being explored for parasite control (Tomilov et al, 2007).…”
Section: The Usefulness Of Rnai As a Cross-species Parasitic Plant Comentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the host-parasite junction of Cuscuta pentágona with tomato, several mRNAs were found to move from host to the dodder [180,181]. Some of the genes with mobile transcripts have roles in mediating plant response to the environment [180], and were proposed to allow some coordination between the parasite and its host [181]. This observation provides the potential to use gene-silencing technologies to increase resistance of crop plants against parasites by exploiting the interspecific trafficking of small interfering RNAs to target vital functions in the parasite.…”
Section: Rnas Species and Traffickingmentioning
confidence: 99%
“…Gene silencing signals containing siRNAs also traffic within a plant to mediate systemic RNA silencing as a means of antiviral defense (Ding and Voinnet, 2007;Kalantidis et al, 2008). RNA trafficking also occurs between some parasitic plants and their hosts, with biological functions yet to be understood (Roney et al, 2007;David-Schwartz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%